The Development of Peasants’ Reading Habits in Courland and Livonia in the 18th Century* - Daija, Pauls (Knygotyra, 2021)
The article explores the development of peasants’ reading habits over the 18th century in the Latvian-inhabited Lutheran regions of Russia’s Baltic provinces Courland/Kurzeme and Latvian Livonia/Vidzeme. By analysing the transition from intensive to extensive reading patterns, as well as from loud and ceremonial to silent and private reading, insight into the available statistical sources and information from subscription lists is provided and the observations of contemporaries are scrutinized. The views on Latvian peasants’ reading habits expressed by Baltic-German Lutheran parsons Friedrich Bernhard Blaufuß, Joachim Baumann, Christian David Lenz, Johann Friedrich Casimir Rosenberger, Alexander Johann Stender, as well as those published by Johann Friedrich Steffenhagen, are discussed within the context of urban and middle-class reading patterns. While the number of literate peasants in the 18th century was high, reaching one third in Courland and two thirds in Livonia by the turn of the 19th century, the motivation for reading and everyday habits differed, and while extensive reading increased, before the 1840s, the Baltic rural society did not see a phenomenon similar to the European middle-class reading revolution. The article focuses on differentiating among various types of readers, divided according to their confessional lines (Herrnhutian Brethren or Lutheran Orthodox Church), social standing (reading patterns were different depending on rural professions) or generation (the older generation tended to prefer loud and ceremonial religious reading while the younger generation more often adopted silent, private and secular reading). The collective reading of books has been explored by demonstrating how it allowed combining the reading of books with other activities and also performed a socializing function. The available sources demonstrate that quiet reading did not replace reading aloud, in the same way that extensive reading did not replace intensive, but all reading practices continued to co-exist alongside each other, creating an increasingly diverse and saturated reading experience.
Keywords: history of reading; enlightenment; reading revolution; Latvian literary culture; Baltic Germans